The role of empowering organization capabilities on efficiency of new product development - Hoda Nikakhtar; Reza Aghamousa; Fataneh Alizadeh Meshkani (Management Science Letters)
This paper presents an empirical investigation on the effects of empowering organizational capabilities on new product-development efficiency improvement and the proposed study is applied in one of Iranian food producers in city of Tehran, Iran. The study considers seven components including technological capabilities, marketing mix capabilities, capabilities for communication with customers, quality of new products, fast entry to market capabilities, customer satisfaction and economic success. The study designs a questionnaire in Likert scale and distributes it among 384 randomly selected people who regularly use different food products. Cronbach alphas for all components of the survey are within acceptable limits and it confirms the overall questionnaire in terms of various questions. The study has used t-student test as well as structural equation modeling to examine different hypotheses of the survey.